Nematode Predation and Competitive Interactions Affect Microbe-Mediated Phosphorus Dynamics - Jie Zheng; Francisco Dini-Andreote; Lu Luan; Stefan Geisen; Jingrong Xue; Huixin Li; Bo Sun; Yuji Jiang (mBio, 2022)
ABSTRACT Nematode predation plays an essential role in determining changes in the rhizosphere microbiome. These changes affect the local nutrient balance and cycling of essential nutrients by selectively structuring interactions across functional taxa in the system. Currently, it is largely unknown to what extent nematode predation induces shifts in the microbiome associated with different rates of soil phosphorous (P) mineralization. Here, we performed an 7-year field experiment to investigate the importance of nematode predation influencing P availability and cycling. These were tracked via the changes in the alkaline phosphomonoesterase (ALP)-producing bacterial community and ALP activity in the rhizosphere of rapeseed. Here, we found that the nematode addition led to high predation pressure and thereby caused shifts in the abundance and composition of the ALP-producing bacterial community. Further analyses based on cooccurrence networks and metabolomics consistently showed that nematode addition induced competitive interactions between potentially keystone ALP-producing bacteria and other members within the community. Structural equation modeling revealed that the outcome of this competition induced by stronger predation pressure of nematodes was significantly associated with higher diversity of ALP-producing bacteria, thereby enhancing ALP activity and P availability. Taken together, our results provide evidence for the importance of predator-prey and competitive interactions in soil biology and their direct influences on nutrient cycling dynamics. IMPORTANCE Nematode predation plays an essential role in determining the rhizosphere microbiome. In doing so, predation dynamically affects the soil nutrient cycling, for instance, by shifting the availability of phosphorus (P) for plant uptake. However, the role of nematode predation inducing selective changes in the microbiome and affecting rates of P mineralization remains still largely unknown. Here, we used a field site treated with different fertilizers to investigate the importance of nematode predation influencing P availability and plant productivity, via changes in bacterial taxa producing alkaline phosphomonoesterases (ALP) and ALP activity in the rhizosphere of rapeseed. We integrated field and laboratory experiments to show that nematode predation induces bacterial keystone taxa to compete with the connected members and results in the modulation of ALP-producing bacterial populations and ALP activity in the rhizosphere. Taken together, our study provides novel insights into microbially mediated mechanisms of competitive interaction induced by nematode predation in enhancing P availability in the plant rhizosphere.